Empowerment of Small-Scale Fishermen in Labuan Salumbone Village, Labuan Sub-District, Donggala District: Pemberdayaan Nelayan Skala Kecil di Desa Labuan Salumbone Kecamatan Labuan Kabupaten Donggala - Mardjudo, Ahsan; Abadiah, Ani Khuyatul; Usman, Hasrudin; Madinawati, Madinawati (Yayasan Ahmar Cendekia Indonesia, 2025)
The purpose of community service activities is to empower fishing communities through training in making bubu as a fishing gear that is generally used by local fishermen. Bubu fishing gear is made of woven bamboo in a rectangular shape. It is a type of fishing gear used by local fishermen to catch demersal fish (local: stone fish). Through community service activities, it is expected to improve the skills of fishing communities in the region. The specific target is to train 30 fishermen from Labuan Salumbone village. The method developed in the implementation of this service activity is education and training in making bubu fishing gear. Education and training in making bubu is an activity to introduce and train fishing communities in making bubu as a fishing gear that can produce catches of various types of fish. In addition, this activity uses a learning by doing approach through groups that have been trained, namely learning while working / doing business. The implementation of community service activities begins with the socialization process of community service activities by the service team from the Alkhairaat University Faculty of Fisheries lecturers and lecturers of the Tadulako University Aquaculture study program. This socialization aims to introduce the community to the activities that will be carried out. Furthermore, training activities for making bubu were carried out which were attended by 23 fishermen.